Efeito da contagem de células somáticas e contagem bacteriana total sobre os constituintes do leite - Vargas, Diego Prado de (2012)
The study aims to evaluate the effect of somatic cell count (SCC) and total bacterial count (TBC) on the constituents of milk, checking the influence that the climatic variables have on these hygienic-sanitary indicators. Data were obtained from 1,541 dairy farms located in 15 municipalities in the dairy region of Vale do Taquari, Rio Grande do Sul. It was tabulated the data from somatic cell count (SCC), total bacterial count (TBC) and milk composition, from June 2008 to December 2011, totaling 44,089 samples. The ambient temperature showed positive and significant correlation to score of somatic cell, while rainfall and relative humidity air showed no correlation. Moreover, the climatic variables have no significant correlation to the TBC. The fat, protein, minerals and total solids were directly correlated with the SCC and TBC, while solids-not-fat and lactose showed an opposite behavior. The principal component analysis (PCA) followed by agglomerative hierarchical clustering method, have showed that milk from SCC 401,000 to 750,000 cell mL-1 and TBC from 100,000 to 1,000,000 CFU mL-1, have the same quality, not justifying stratification in these intervals. In addition, it was observed that only limits regulatory standards are not sufficient to improve the quality of milk, suggesting parameters for payment system based on the bonus and penalty relative to the TBC and SCC milk.